The Anabaptist vision - Bender, Harold Stauffer, 1897-1962 (Herald Press, 1944)
The Anabaptist Vision, given as a presidential address before the American Society of Church History in 1943, has become a classic essay. In it, Harold S. Bender defines the spirit and purposes of the original Anabaptists. Three major points of emphasis are: the transformation of the entire way of life of the individual to the teachings and example of Christ, voluntary church membership based upon conversion and commitment to holy living, and Christian love and nonresistance applied to all human relationships.